Tingkat Efisiensi Penggunaan Resep Dokter Spesialis Menggunakan Metode K-Means Clustering - Sharon; Sarjon Defit; Gunadi Widi Nurcahyo (Jurnal Informasi dan Teknologi, 2021)
The National Formulary (Fornas) is a list of drugs stipulated in a Decree of the Minister of Health of the Republic of Indonesia, which is used as a guideline for hospitals in drug supply for participants of the National Health Insurance (JKN) program. Doctor's prescription is one indicator of the quality of hospital services. Prescribing drugs based on guidelines will provide efficiency in the supply of drugs. The purpose of this study was to facilitate controlling drug supplies, safe use of drugs and control costs and quality of treatment. K-Means Clustering is a method of grouping data into clusters using the K-Means algorithm. The data used in this study was a specialist doctor's prescription in December 2019 which was sourced from the Pharmacy department of the Meranti Islands District Hospital. The results of this research with the K-Means Clustering method consisted of 3 (three) clusters, namely cluster 0 obeying Fornas as many as 2 polyclinics, cluster 1 being less obedient to Fornas as many as 2 polyclinics and cluster 2 not obeying Fornas as many as 3 polyclinics. This research can be used as a reference and evaluation to hospital management on the efficiency level of using specialist doctor's prescriptions in improving the quality of hospital services.